2018
DOI: 10.1177/2325967118771616
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Extravasation in Shoulder Arthroscopic Surgery: A Systematic Review

Abstract: Background:Arthroscopic surgery of the shoulder joint has become increasingly more common given its advantages over open surgery; however, one rare but potentially life-threatening complication is fluid extravasation into the surrounding tissues, causing edema, respiratory compromise, abnormal results on laboratory blood tests, and possibly death. Currently, no systematic review exists that summarizes the existing clinical research on this topic.Purpose:To perform a systematic review on fluid extravasation as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 38 publications
2
45
1
Order By: Relevance
“…The authors also suggest limiting the pump pressures to less than 150 mmHg. Utilizing a gravity feed irrigation setup may be a safer alternative to pump systems which result in higher intra-articular pressures [1618]. Their literature review also found that symptomatic patients had irrigation volumes of between 20 and 36 L and suggest limiting the total irrigation volume to 20 L. [16]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also suggest limiting the pump pressures to less than 150 mmHg. Utilizing a gravity feed irrigation setup may be a safer alternative to pump systems which result in higher intra-articular pressures [1618]. Their literature review also found that symptomatic patients had irrigation volumes of between 20 and 36 L and suggest limiting the total irrigation volume to 20 L. [16]…”
Section: Discussionmentioning
confidence: 99%
“…Total operative time is directly proportional to the volume of irrigation fluid used and subsequent weight gain by the patient, presumably from absorption of the irrigation fluid [19]. Although there is no clear safe upper limit for operative times, some authors suggest limiting surgical time to between 90 and 120 min to reduce this risk [16, 20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For swelling of adjacent neck, chest, and facial tissues, most patients will be lack of obvious syndrome within 2 days after surgery. [ 2 ] However, in severe cases, excessive irrigation will flow into the pharyngolaryngeal and paratracheal space, which can lead upper respiratory obstruction [ 3 , 4 ] and even pulmonary edema. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it may lead the occurrence of signi cant edema of face, neck and chest tissues, tracheal compression, upper respiratory tract obstruction, and pulmonary edema. For swelling of adjacent neck, chest, and facial tissues, most patients will be lack of obvious syndrome within 2 days after surgery [2]. However, in severe cases, excessive irrigation will ow into the pharyngolaryngeal and paratracheal space, which can lead upper respiratory obstruction [3,4] and even pulmonary edema [5].…”
Section: Introductionmentioning
confidence: 99%